Is Current Way of Promoting Sustainability, Sustainable?. Issue 1 (1st January 2019) - ShabbirHusain, R.V.; Varshney, Sanjeev
ABSTRACT: Consumer behavior regarding sustainable products has been a complex concept. There is a discrepancy between consumer's espoused concern towards environment and their purchase of environment friendly products. Past literature suggests greenwashing being a possible reason for this discrepancy. With greenwashing being caused by mismatch between communication and perceived performance, this article focuses on assessment of simultaneous impact of both communication and performance elements on brand attitude. A quantitative study was undertaken to test the hypotheses. This was followed by a qualitative study to understand alternative explanation of hypotheses that was not accepted. The research revealed that a consumer's attitude toward a green brand is impacted both by his or her general skepticism towards green ads and the credibility that she assigns to the firm's green message. Perceived value of product also had a positive impact on brand attitude. Findings advance academic literature and support managerial community by highlighting factors for building a positive green brand attitude and resultantly avoiding the trap of being equated with greenwashing.